Radiographic, computed tomographic, and arthroscopic findings in Labrador Retrievers with medial coronoid disease - Lau, Seng Fong; Theyse, Lars Frederik Herman; Voorhout, George; Hazewinkel, Herman A.W. (Wiley-Blackwell Publishing, Inc., 2015)
Objective To describe the radiographic, computed tomographic (CT), and arthroscopic findings in different age groups of Labrador Retrievers diagnosed with medial coronoid disease (MCD), and to compare the ulnar subtrochlear sclerosis (STS) observed on radiographs with the ratio between the mean attenuation of the ulnar subtrochlear bone and the mean attenuation of the cortical bone measured on CT. Study Design Prospective clinical study. Animals Dogs (n = 31; 31 elbow joints) and 6 healthy Labrador Retrievers (6 elbow joints). Methods Radiographic, CT, and intraoperative arthroscopic images (2008–2012) were evaluated. Statistical analysis was performed for the descriptive study to evaluate the difference in findings between age groups and to investigate the correlation between radiographic and CT evaluated ulnar STS. Results Ulnar STS (87.6%) was the most common radiographic findings in dogs ≤12 months and blurring of the cranial edge of the medial coronoid process (MCP; 66.7%) was the most common radiographic findings in dogs >12 months. MCP fragmentation was the most common CT finding in both age groups (93.8% [≤12 months]; 66.7% [>12 months]). A displaced fragment (68.8%) was the most common arthroscopic finding in dogs ≤12 months whereas osteochondromalacia (53.3%) was the most common finding in dogs >12 months. Sensitivity of radiography in detecting MCD was 93.8% (≤12 months) and 73.3% (>12 months) and for CT was 93.8% (≤12 months) and 66.7% (>12 months). Radiographic evaluated ulnar STS was strongly correlated with CT evaluated ulnar STS. Conclusion Wide ranges of radiographic, CT, and arthroscopic findings in Labrador Retrievers diagnosed with medial coronoid disease were identified.